Use Of Herbal Medicine Materials In Healing Perineal Rupture Wounds In Baros Health Center, Serang, Banten 2022 - Mudiyati Mudiyati; Maryati Sutarno (CV. Inara, 2023)
Introduction: Indonesia has many regions that still use plants as traditional medicines which are a hereditary inheritance which until now has been widely used in treating various diseases, both acute and chronic. At the Baros Health Center, data obtained on the healing of perineal wounds that experienced complications were 27% in 2020, increasing to 45% in 2021. The use of wound healing plants is widely used, including betel leaves and gotu kola leaves. In this study, it was tested which one was more effective in healing wounds among the herbal medicinal plants. Research Method: The design of this research is an analytic survey using cross sectional with chi square statistical test. Sampling was carried out by total sampling method from all samples of 30 respondents. Results: Obtained a cure rate in the group using betel leaf decoction of 68.7%, this is greater than the use of gotu kola leaves which only has a cure rate of 31.2%. The analysis obtained a p-value of 0.028 and an Odds ratio: 5.500, which means that the healing rate when using betel leaf is 5x faster than gotu kola leaves. Conclusion: Betel leaf is a plant that grows in Indonesia and is effective in helping accelerate the healing process of grade 2 perineal wounds compared to using gotu kola leaves.